Scalable networks of multimodal haptic arrays for plantar sensory substitution - Matthew T. Flavin; Yu-Ting Huang; Dimitrios Simatos; Rui Hua; Shreya Aalla; Jesse Cornman; Richa Rai; Jihun Park; Chinmay Bandapalli; Tara Saxena; Molly Henry; Joseph Harris; et al. (Proceedings of the National Academy of Sciences, 2026)
Feet provide essential sensory input, supporting body awareness for safe movement. The impairment of plantar sensation, arising in conditions such as stroke and spinal cord injury, has a major impact on mobility, balance, and quality of life. Substituting the sensation of plantar pressure to another area on the body with intact somatosensory abilities requires capabilities for fast, programmable delivery of haptic feedback. Here, we introduce a wireless network of skin-conformable, multimodal haptic arrays that deliver high-density thermal and vibrotactile patterns anywhere on the body. Central to this approach is a hybrid motor unit that independently controls thermal and mechanical stimulation, enabling 128 degrees of freedom across 64 addressable nodes. Electromechanical characterization establishes precise, simultaneous, and safe modulation of both modalities. Psychophysical experiments demonstrate reliable spatial discrimination of colocated heat and vibration. These haptic arrays form the receivers in a sensory substitution system that delivers patterns of vibrotactile stimulation to mirror the distribution of pressure recorded from an insole-based array of pressure sensors. Exploratory case studies in individuals with spinal cord injury and stroke demonstrate feasibility and suggest improved performance during standing balance and walking tests. Altogether, this work highlights the potential of information-rich cutaneous interfaces to substitute plantar sensation, expanding the scope of somatosensory engagement for rehabilitation, entertainment, and education.